PENGARUH KAMPANYE SARAPAN PAGI SEHAT DENGAN MEDIA KOMIK TERHADAP PERUBAHAN PERILAKU SARAPAN PAGI SISWA SD NEGERI 060880 KECAMATAN MEDAN POLONIA TAHUN 2016 - Dyanika Putri; Zulhaida Lubis; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Habit of breakfast is included in one of the thirteen basic message of balanced nutrition. For school children breakfast sufficient proven to improve learning concentration and stamina thus improving learning achievement. Often school children ignore breakfast on the grounds of lack of time, not hungry or no appetite. Though breakfast is not just a booster stomach, but the breakfast also provides energy for the body to move with optimal, otakpun optimized to work with and not get sleepy. The aim of this research to find out effect of a healthy morning breakfast campaign with the comic media to changes in knowledge and attitudes breakfast for elementary school student 060880 districts Medan Polonia. This type of research is quasi experiment (quasi-experiment) with the draft One Pretest-Posttest Group Design. Total sample are 74 children which fluently reading. Using questionnaires and data collection to data analysis using testpaired t test, The result of the analysis showed that the change in the behavior of a healthy breakfast every morning with comics as a media campaign giving healthy breakfast, as seen from the increase in the average value of the knowledge and attitudes of children in public primary schools 060880 District of Medan Polonia. It is suggested to the health center in collaboration with the School Health Unit (UKS) can use the comics medium as a communication medium nutrition in educational activities and health education about healthy breakfast to change the behavior of elementary school students in eating a healthy breakfast in the morning before the activity. Keywords: healthy breakfast, comics media, knowledge, attitudes, elementary school students